ADSORPTION ISOTHERM OF HYDROGEN SULFIDE ON AN ACTIVATED ADSORBENT DERIVED FROM HYBRID PAULOWNIA TOMENTOSA WOOD - Bakhronov, Khayot; Aliyeva, Mukhayyo; Kokharov, Mirzokhid; Sultonov, Amirkhon; Jumaeva, Dilnoza; Jumaboeva, Zebo; Gaybullayeva, Dildora; Abdumutalova, Gulrux (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study presents the results of investigating the adsorption isotherms of hydrogen sulfide on a carbonaceous adsorbent derived from Paulownia tomentosa (woolly paulownia) wood using the steam–gas activation method. The thermodynamic and structural parameters of the sorbent were examined, which determine its high sorption capacity and chemical stability during interaction with H₂S. Steam–gas activation of Paulownia tomentosa charcoal was carried out at controlled temperatures (700–850 °C) using water vapor as the activating agent. The resulting adsorbent exhibited a well-developed microporous structure and a high specific surface area (up to 1100 m²/g). The adsorption isotherms of H₂S at 303 K were studied using microcalorimetry and static adsorption methods. It was found that the adsorption process is of a physico-chemical nature, indicating a predominantly monomolecular mechanism of interaction. Analysis of the linear portion of the adsorption isotherm showed that the number of active sites on the adsorbent surface is 0.54 mmol/g. This value reflects the high activity of the microporous structure and the presence of polar functional groups on the sorbent surface. Furthermore, the results indicate that the interaction between the adsorbate and the adsorbent occurs through the formation of a complex in a 3:1 ratio (3H₂S:C) at the active sites. Such an interaction pattern suggests a monomolecular adsorption mechanism of H₂S and confirms the high selectivity, stability, and efficiency of the carbonaceous adsorbent in gas purification processes. The obtained results demonstrate that steam-activated carbon derived from Paulownia tomentosa is a promising sorbent for hydrogen sulfide removal from gas streams, offering high capacity, stability, and environmental safety. This work opens opportunities for further optimization of activation conditions and surface modification to enhance the efficiency of natural and industrial gas purification.